Assessment of micronutrient situation among reproductive-age women (15-49) and under-five children in Sudan - Swareldhab, Eiman S. elkhalifahassan; Al-Jawaldeh, Ayoub; Qureshi, Abdul Baseer; Ali, Amira M. Elmunier; Abu-Manga, Mohamed; Al-Areeqi, Maha; Dureab, Fekri (Nutrients, 2021)
Background: Micronutrient malnutrition is a form of undernutrition that causes diseases, and this is mainly due to insufficient intake of nutrients in daily foods. The status of micronutrients for people in Sudan remains scarce, and information is limited. The aim of this study is to highlight the status of micronutrients among women of reproductive age (15-49 years of age) and their children in Sudan. Methods: This manuscript is a quantitative descriptive study, based on the data from Sudan Micronutrient Survey (SMS); it is part of the second round of the Simple Spatial Survey Method (S3M II) in Sudan (a total of 93,882 households). Results: The level of consumption of vitamin A-rich foods was found to be moderate at 67.36% for reproductive-age women and low at 23.44% for under-five children. Similarly, consumption rate of vitamin B-rich foods among reproductive-age women was 62.13%, and low for children at 11.02%. The consumption of iron-, calcium-, and zinc-rich foods was moderate among women (66.75%, 47.69%, 69.72%, respectively) and very low in children (12.28%, 17.62%, 14.99%, respectively). The iron deficiency prevalence was 47% in non-pregnant women, 58% in pregnant women, and 54% in children. The prevalence of anemia was 30% in non-pregnant women, 37% in pregnant women, and 48% in children. Generally, urinary iodine concentration was inadequate in lactating and non-pregnant women as well as in pregnant women. Most indicators of micronutrients in Sudan for children and women of reproductive age were highly significant. Sudan needs more efforts to create an enabling environment through legislation, policies, and strategies to strengthen the nutrition-sensitive and specific interventions and improving status of micronutrients among women and children, focusing on food fortification, food supplements, and counseling on micronutrients intake for mothers during antenatal and postnatal services as well as raising community awareness.
Gesehen am 22.10.2021